Georeferenced data in epidemiologic research - Guilherme Loureiro Werneck (Ciência & Saúde Coletiva, 2008)
Abstract This paper reviews some conceptualand practical issues regarding the application ofgeoreferenced data in epidemiologic research.Starting with the disease mapping tradition ofgeographical medicine, topics such as types of georeferenceddata, implications for data analysis,spatial autocorrelation and main analytical approachesare heuristically discussed, relying onexamples from the epidemiologic literature, mostof them concerning mapping disease distribution,detection of disease spatial clustering, evaluationof exposure in environmental health investigationand ecological correlation studies. As for concludingremarks, special topics that deserve furtherdevelopment, including the misuses of theconcept of space in epidemiologic research, issuesrelated to data quality and confidentiality, therole of epidemiologic designs for spatial research,sensitivity analysis and spatiotemporal modeling,are presented.